Ответы 1

  • Упростим выражение:

    А) -2 * а^5 * х * 0,5 * а^2 = -2 * 0.5 * (a^5 * a^2) = -2 * 1/2 * a^5 * a^2 = -1 * a^5 * a^2 = -a^5 * a^2 = -a^(5 + 2) = -a^7;  

    Значит,  -2 * а^5 * х * 0,5 * а^2 = -a^7. 

    б) -3 * а^7 * у^2 * 0,5 * а * у^3 = -3 * 0.5 * a^7 * a * y^2 * y^3 = -4.5 * a^(7 + 1) * y^(2 + 3) = -4.5 * a^8 * y^5; 

    Значит,  -3 * а^7 * у^2 * 0,5 * а * у^3 = -4.5 * a^8 * y^5. 

    • Автор:

      lilly26
    • 3 года назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years